Informal Traffic Controller: Study on Shadow Economy in Indonesia - Chalid, Pheni; Kuswini, Isniati (Signifikan: Jurnal Ilmu Ekonomi, 2023)
The urban low-income segment of society survived on their earnings in the informal sector. This study examines the informal traffic controllers in the shadow economy framework who assist incoming cars at traffic-congested intersections and turning lanes in the main cities to earn income. This paper originates from the preliminary study of “Pak Ogah”: the Portrait of Shadow Economy in the Greater Area of Jakarta. The field study was conducted at 60 congested intersections and turning lanes on roadways where the informal traffic controller groups operated. The study employs a mixed method of qualitative and quantitative procedures and conducts a triangulation strategy. The study's implications suggest that the shadow economy was created by institutional failure to anticipate the negative impact of urban development policy.JEL Classification: O17, E26, R41, I32How to Cite:Chalid, P., & Kuswini, I. (2023). Informal Traffic Controller: Study on Shadow Economy in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 399-412. https://doi.org/10.15408/sjie.v12i2.33434.